2015
DOI: 10.1038/cddis.2015.47
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial cancer-associated mutants of SPOP are defective in regulating estrogen receptor-α protein turnover

Abstract: Increasing amounts of evidence strongly suggests that dysregulation of ubiquitin-proteasome system is closely associated with cancer pathogenesis. Speckle-type POZ protein (SPOP) is an adapter protein of the CUL3-based E3 ubiquitin ligase complexes. It selectively recruits substrates for their ubiquitination and subsequent degradation. Recently, several exome-sequencing studies of endometrial cancer revealed high frequency somatic mutations in SPOP (5.7–10%). However, how SPOP mutations contribute to endometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 25 publications
1
54
0
Order By: Relevance
“…Codons F102, W131, F133 and K134 are mutated mostly in prostate cancers and E47 and E50 are altered in endometrial cancers (27, 28, 31). Recently, SPOP was shown to induce ubiquitination and degradation of androgen receptor and ERG in prostate cancer and estrogen receptor-α in endometrial cancer, but the SPOP mutants were impaired in this ubiquitination activity (29, 30, 32, 33). When we looked for alleles correlated to the E50K, loss-of-function allele in endometrial cancer (32), E47A was highly correlated, suggesting that this allele may also be a loss-of-function allele (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Codons F102, W131, F133 and K134 are mutated mostly in prostate cancers and E47 and E50 are altered in endometrial cancers (27, 28, 31). Recently, SPOP was shown to induce ubiquitination and degradation of androgen receptor and ERG in prostate cancer and estrogen receptor-α in endometrial cancer, but the SPOP mutants were impaired in this ubiquitination activity (29, 30, 32, 33). When we looked for alleles correlated to the E50K, loss-of-function allele in endometrial cancer (32), E47A was highly correlated, suggesting that this allele may also be a loss-of-function allele (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3F). To further exclude the possibly indirect effect of SPOP-targeting other substrates, such as ER and AR [32,41], we revealed that SPOP -deficiency could largely increase EglN2 protein instead of mRNA levels in AR-null PC3 cells (Fig. 3G and H).…”
Section: Resultsmentioning
confidence: 99%
“…Truncated SPOP constructs encoding the BTB and BACK domains self‐associate into higher‐order oligomers (Errington et al , 2012) that possess increased ubiquitination efficiency, supporting the functional importance of oligomerization (Zhuang et al , 2009; Errington et al , 2012). Mutations within the MATH domain perturb interactions with substrates (Geng et al , 2013, 2014; Theurillat et al , 2014; Zeng et al , 2014; Zhang et al , 2015). Mutations within both self‐association domains are also found in cancers [Appendix Fig S1 and www.cbioportal.org (Cerami et al , 2012; Gao et al , 2013)], further supporting a functional role for higher‐order oligomerization, but their pathological mechanism is unclear.…”
Section: Introductionmentioning
confidence: 99%